Liability for Providing Hyperlinks to Copyright-Infringing Content: International and Comparative Law Perspectives - Ginsburg, Jane C.; Budiardjo, Luke Ali (The Columbia Journal of Law & the Arts, 2018)
Hyperlinking, at once an essential means of navigating the Internet, but also a frequent means to enable infringement of copyright, challenges courts to articulate the legal norms that underpin domestic and international copyright law, in order to ensure effective enforcement of exclusive rights on the one hand, while preserving open communication on the Internet on the other. Several recent cases, primarily in the European Union, demonstrate the difficulties of enforcing the right of communication to the public (or, in U.S. copyright parlance, the right of public performance by transmission) against those who provide hyperlinks that effectively deliver infringing content to Internet users. This Article will first address the international norms that domestic laws of states members to the multilateral copyright agreements must implement. It next will explore how two of the most significant regional or national copyright regimes, the E.U. and the U.S., have coped with the question of linking, and then will consider the relationship of the emerging approaches to copyright infringement with national and regional laws instituting limited immunity for copyright infringements committed by internet service providers. We will conclude with an assessment of the extent to which the outcomes under U.S. and E.U. regimes, despite their apparently different approaches, in fact converge.